2014
DOI: 10.1073/pnas.1323016111
|View full text |Cite
|
Sign up to set email alerts
|

Spatial constraints control cell proliferation in tissues

Abstract: Significance Spatiotemporal coordination of cell growth underlies tissue development and disease. Mechanical feedback between cells has been proposed as a regulatory mechanism for growth control both in vivo and in cultured cells undergoing contact inhibition of proliferation. Evidence beyond theoretical and correlative observations falls short. In this study, we probe the impact of mechanical tissue perturbations on cell cycle progression by monitoring cell cycle dynamics of cells in tissues subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
230
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(259 citation statements)
references
References 50 publications
28
230
1
Order By: Relevance
“…It has been shown experimentally that a high cell density can impair cell division through contact inhibition of proliferation (41). Furthermore, it was shown that stretching of epithelial sheets can induce cell cycle progression (42). The idea that an optimal pressure for cell division, called homeostatic pressure, exists was postulated in theoretical studies (43).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown experimentally that a high cell density can impair cell division through contact inhibition of proliferation (41). Furthermore, it was shown that stretching of epithelial sheets can induce cell cycle progression (42). The idea that an optimal pressure for cell division, called homeostatic pressure, exists was postulated in theoretical studies (43).…”
Section: Resultsmentioning
confidence: 99%
“…Clones compete for space in a complex process termed "clonal interference" (Garcia et al 1999;Baker et al 2013;Streichan et al 2014;Greaves 2015). Because of minimal information on mutational event timing and spatial pervasiveness in past studies based on single time points (Maley et al 2004), it is uncertain if mutant clone "sweeps to fixation" occur as a defining feature of premalignant disease.…”
Section: Quantifying the Pace And Pattern Of Evolutionmentioning
confidence: 99%
“…When coordinated across a tissue, these active cellular processes and passive responses enable epithelial sheets to undergo shape changes while retaining relatively normal cell packing (6) and help return tissues to their resting state following a perturbation (7). Although the molecular basis of this cooperation is not understood, several studies have suggested a role for mechanical feedback (8,9). Cell division has been suggested to participate in this feedback (10) because the rate of animal cell proliferation responds to changes in extrinsic forces in several experimental settings (9).…”
mentioning
confidence: 99%
“…Although the molecular basis of this cooperation is not understood, several studies have suggested a role for mechanical feedback (8,9). Cell division has been suggested to participate in this feedback (10) because the rate of animal cell proliferation responds to changes in extrinsic forces in several experimental settings (9). Further, division makes an important contribution to tissue morphogenesis in animals (11,12), accounts for much of the topological disorder observed in epithelia (13), can drive tissue elongation (10), and can facilitate the return to homeostatic cell packing following a deformation (2).…”
mentioning
confidence: 99%